2014
DOI: 10.1177/0956462414521162
|View full text |Cite
|
Sign up to set email alerts
|

Social and behavioural risk factors for HIV infection among the wives of labour migrants in Nepal

Abstract: Summary Labour migration has increased the risk of HIV infection among the wives of labour migrants in Nepal. We conducted a matched case-control study to identify the social and behavioural factors for HIV infection among the wives of labour migrants in Nepal. We interviewed 112 wives of labour migrants diagnosed with HIV (cases) and 112 wives of labour migrants testing negative for HIV (controls) and used logistic regression analysis to assess independent factors associated with HIV infection. Literacy statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…Occurrence of sexually transmitted infections in women strongly depends on their husband's sexual behavior . Although a previous study from Nepal reported a high risk of HIV infection among wives of migrants , we did not find an association between the husbands' residence and HPV infection in their spouse. The higher prevalence of HR‐HPV infection among current smokers in our study is consistent with the results of a large multicenter study that showed increasing risk of HPV positivity with higher smoking intensity .…”
Section: Discussioncontrasting
confidence: 99%
“…Occurrence of sexually transmitted infections in women strongly depends on their husband's sexual behavior . Although a previous study from Nepal reported a high risk of HIV infection among wives of migrants , we did not find an association between the husbands' residence and HPV infection in their spouse. The higher prevalence of HR‐HPV infection among current smokers in our study is consistent with the results of a large multicenter study that showed increasing risk of HPV positivity with higher smoking intensity .…”
Section: Discussioncontrasting
confidence: 99%
“…First, in the sensitivity analysis of all sexually active women (i.e., not only women with linked partners), we obtained broadly similar findings. Second, we observed greater adverse impacts of food insecurity among women with migrant partners, which is notable given that migrants are a particularly vulnerable and high-risk sub-population in Nepal's HIV epidemic [47]. The bulk of the sizeable migrant worker population in Nepal consists of men, who may be gone for months or even years at a time [48].…”
Section: Discussionmentioning
confidence: 99%
“…Women who live in rural areas where plowing is a taboo activity [51] may experience considerable livelihood insecurity and economic dependence on men and may therefore be at even greater risk for HIV acquisition [50]. Definitive conclusions about whether Nepal's HIV epidemic is beginning to expand out of high-risk groups [31] and the extent to which migrant workers may act as a “bridge” to subgroups not typically thought of being at risk for HIV acquisition [47,50], however, are constrained by the poor quality of available epidemiological evidence on HIV and sexual behavior in Nepal as a whole [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Women having migrant husband who did not ever attend school were likely 5.87 times higher to get HIV. 15 Meanwhile, the women who had husband never attending school were likely 5 times higher to get HIV. Quinn and Overbaugh, 6 stated that lower education was one of the roots of women vulnerability toward HIV infection.…”
Section: Discussionmentioning
confidence: 99%